Aplikasi Sistem Monitoring Pengairan Sawah Subak Berbasis Android - Ni Made Ary Esta Dewi Wirastuti; Zaky Zamani Noor; Komang Oka Saputra (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
Subak is a group of farmers in Bali to manage rice fields irrigation. Farmers come directly to the rice fields which need time to monitor their fields irrigation so that it’s less efficient. Based on this, an Android-based subak irrigation monitoring application was designed using the flutter framework with subak culture system for monitoring farmers fields irrigation and using supporting application namely Android Studio. The result of this research is an Android application that can display the location of the rice fields that registered, successfully sends a high water request, successfully sends a request for registration of subak fields, and successfully reports damages in case of damages to the fields and also successfully retrieves data on the condition of rice fields whose data is taken from the Antares database. The Black-box testing and System usability scale (SUS) used in the Android application has been successfully run according to the given scenario and functions and also suitable for use by users because the result of SUS are above the average value that is 72.875.